Metabolic acidosis in a lactating woman induced by a deliberate ketogenic diet. Issue 12 (December 2021) - Hong, Michelle J.; Schwartz, Lauren E.; Ward, Hillary H.; Morgan, Jason C.; Jacoby, Jeanne L.
Abstract : ABSTRACT: This article describes a rare case of lactation ketoacidosis in a patient who started a ketogenic diet while nursing an infant and toddler. The patient presented to the ED with a history of nausea, vomiting, and postural dizziness, and was found to have a significant metabolic acidosis and elevated lipase level. The metabolic changes induced in this patient could occur in anyone with high metabolic demands who also is on a strict ketogenic diet. The case highlights the importance of a dietary history in patients with unexplained metabolic derangements.